Interferon-gamma (IFN-γ)-mediated retinal ganglion cell death in human tyrosinase T cell receptor transgenic mouse. - Shahid Husain; Yasir Abdul; Christine Webster; Shilpak Chatterjee; Pravin Kesarwani; Shikhar Mehrotra (PLoS ONE)
We have recently demonstrated the characterization of human tyrosinase TCR bearing h3T-A2 transgenic mouse model, which exhibits spontaneous autoimmune vitiligo and retinal dysfunction. The purpose of current study was to determine the role of T cells and IFN-γ in retina dysfunction and retinal ganglion cell (RGC) death using this model. RGC function was measured by pattern electroretinograms (ERGs) in response to contrast reversal of patterned visual stimuli. RGCs were visualized by fluorogold retrograde-labeling. Expression of CD3, IFN-γ, GFAP, and caspases was measured by immunohistochemistry and Western blotting. All functional and structural changes were measured in 12-month-old h3T-A2 mice and compared with age-matched HLA-A2 wild-type mice. Both pattern-ERGs (42%, p = 0.03) and RGC numbers (37%, p = 0.0001) were reduced in h3T-A2 mice when compared with wild-type mice. The level of CD3 expression was increased in h3T-A2 mice (h3T-A2: 174 ± 27% vs. HLA-A2: 100%; p = 0.04). The levels of effector cytokine IFN-γ were also increased significantly in h3T-A2 mice (h3T-A2: 189 ± 11% vs. HLA-A2: 100%; p = 0.023). Both CD3 and IFN-γ immunostaining were increased in nerve fiber (NF) and RGC layers of h3T-A2 mice. In addition, we have seen a robust increase in GFAP staining in h3T-A2 mice (mainly localized to NF layer), which was substantially reduced in IFN-γ ((-/-)) knockout h3T-A2 mice. We also have seen an up-regulation of caspase-3 and -9 in h3T-A2 mice. Based on our data we conclude that h3T-A2 transgenic mice exhibit visual defects that are mostly associated with the inner retinal layers and RGC function. This novel h3T-A2 transgenic mouse model provides opportunity to understand RGC pathology and test neuroprotective strategies to rescue RGCs.